THE EFFECT OF TIKTOK APPLICATION USE ON THE PERCEPTION OF VALUES AND NORMS AMONG STUDENTS IN HIGH SCHOOL - Raisya Eliyana Rahya Harahap; Putri Khairunnisa; Roy Bastian Shaputra; Sayyid Faqih Nasution; Salisa Sari Humaira (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the influence of TikTok app usage on high school students' perceptions of values ​​and norms. The quantitative method employed was a survey of 100 respondents at Al-Azhar Medan's flagship high school.indicates a significant influence(p=0.002 ; p<0.05).Based on statistical calculations, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted.The findings show that the frequency and intensity of TikTok use correlate with changes in adolescents' perceptions, particularly regarding informal aspects such as slang and social norms, compared to formal school norms such as discipline. Although TikTok is a powerful socializing agent in shaping adolescents' social views, the educational environment and parental guidance remain the primary foundations for maintaining the integrity of core values.This research is expected to provide a basis for consideration and reference for educators and parents.to design a more effective and proactive digital literacy strategy in guiding the younger generation.